Process Evaluation of the Residential Substance Abuse Treatment (RSAT) Program at the Illinois Youth Center, St. Charles, 1999-2000 - Cowles, Ernest L. ([Verlag nicht ermittelbar], 2002)
As part of the Violent Crime Control and Law Enforcement Act of 1994, Congress provided funding for the development of substance abuse treatment programs in state and local correctional facilities with the Residential Substance Abuse Treatment (RSAT) for State Prisoners Formula Grant Program. To be eligible for this funding, programs were required to last between six and 12 months, be provided in residential treatment facilities set apart from the general correctional population, be directed at the inmate's substance abuse problems, and be intended to develop the inmate's cognitive, behavioral, social, vocational, and other skills to address substance abuse and related problems. The Illinois Youth Center (IYC) in St. Charles started an RSAT program on September 30, 1999. The primary emphasis of this process evaluation was to describe why and how the St. Charles RSAT program was designed, implemented, and operated. To a lesser degree, attention was also directed toward examining the effects of program participation on offender pre-release behavior. This was considered to be a primary indicator of program impact. This project sought to answer the following research questions: (1) Did the program fit within the institutional environment? (2) Was the program operating as a therapeutic community? (3) Were the appropriate offenders selected for program participation? and (4) Were any short-term impacts evident within the youth? This study followed a process evaluation design with a focus on determining how a product or outcome was produced, rather than on assessing the product or outcome itself. Information in this data collection was collected from youth participants and youth files. Subjects consisted of the 44 youths who began the RSAT program in 1999 (the treatment group), as well as a matched sample of non-program participants (the comparison group). The comparison group was used to contrast institutional behavior of youths not in the treatment program and to establish a non-treatment cohort for an expected follow-up impact study. Part 1 contains data from two surveys of program youth only, and Parts 2-4 contained data on both program youth and the comparison group. Part 2 data were gathered from a review of the youths' master files at the correctional facility. Part 3 data were obtained from behavior action tickets (BATs), which were an institution-wide semi-formal mechanism to recognize positive and negative youth behavior. Part 4 data were collected from institutional disciplinary reports (IDRs). Part 1 surveyed youth about what they hoped to achieve in the RSAT program, whether they thought the program would help them, how well they understood the program, how they assessed their own substance abuse problems, what they liked and disliked about the program, their opinions about program staff, and their recommendations for changing the program. Demographic variables in Part 2 include age, race, and education level. Other variables record reading test scores, math test scores, IQ scores, location of parents, number of siblings, drug use and frequency, criminal history, types of prior substance abuse treatments, family history of drug use, suicidal ideations, and personality test scores. Part 3 contains monthly counts of positive and negative behavior action tickets. Part 4 contains information about the number and types of guilty institutional disciplinary reports, the severity of the offenses, and the number and types of punishments received.